Diseño de molde de un bebedero para perros de razas grandes (2018)
For the development of the project, the current state of spruers was analyzed, then the variables of the piece were parametrized; a study of material alternatives was carried out, complying with the requirements to which the product is submitted. Then the mold design was started, giving away a study of alternatives, for the selection of the cooling system, the selection of materials for each element of the mold. It was designed with one of the elements that make up the injection mold by means of solid edge software. The piece was simulated in moldflow is to see the quality and reliability of injection and that way to know if the design of the piece is the correct one for the manufacture, by means of NX the piece was simulated to observe the efforts submitted on the piece. the assembly, operation and maintenance manuals for the injection mold were elaborated. A financial evaluation was made to see the profitability of the project for the company, buying more profits with and without the project.